An evaluation of glutathione transferase associated with Dichlorvos degradation in African palm weevil (Rynchophorus phoenicis) larva. Issue 1 (1st January 2017) - Bamidele, Olufemi Samuel; Ajele, Joshua Oluwafemi; Olajuyigbe, Folasade Mayowa
Abstract: This study was conducted to investigate the metabolic defensive mechanism in the larvae of African palm weevil ( Rynchophorus phoenicis ) administered with dichlorvos (2, 2-dichlorovinyl dimethylphosphate) solution. Bioassay experiment with dichlorvos was conducted on the larva and glutathione-utilizing enzyme activities were determined in the major organs: fat body, gut, and head of R. phoenicis larva 48 h after treatment with 0–0.060 μg g −1 body weight dichlorvos solution. Glutathione transferase was purified from the gut of larvae by ion-exchange chromatography on diethylaminoethyl-Sephadex A50 and affinity chromatography on glutathione-Sepharose 4B columns. The purified enzyme was homogenous as revealed by sodium dodecylsulfate polyacrylamide gel electrophoresis. Initial velocity studies were carried out on the purified enzyme using standard procedures. Bioassay experiment indicated alterations of glutathione peroxidase, glutathione reductase, and glutathione transferase activities in the major organs of larva caused by dichlorvos. Glutathione transferase activity in the gut of larva was three times higher than that of glutathione peroxidase and glutathione reductase activities, an indication of possible detoxification role of glutathione transferase in the organ. A 49.7 kDa homodimeric glutathione transferase was identified from the gut of larva and was tagged rpl GSTc. Mechanism of action of rpl GSTc with 1-chloro-2, 4-dinitrobenzene, and glutathione as substrates conformed to the random sequential mechanism. These results confirmed the presence of GST associated with the degradation of dichlorvos in the gut of R. phoenicis larva.